“US” AND “THEM” IN THINGS FALL APART BY CHINUA ACHEBE: A CRITICAL FUNCTIONAL APPROACH OF OTHERING - Lusia Kristiasih Dwi Purnomosasi; Vastukencana Sih Gita Garudatama; Sigit Ricahyono (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
“Us” and “them” or othering often brings about world’s most feared phenomenon, xenophobia. This qualitative study purposes to disclose attitudinal strategies used in Chinua Achebe’s “things Fall Apart”. An excerpt from it was analysed through the “APPRAISAL”, especially the “ATTITUDE”, and ‘PERIODICITY” theories. Results reveal that “us” is framed with 4 (+) values and only 2 in (-) while “them” is constructed through only 1 (+) value and 3 (-). The vast majority of the attitudinal strategies used is “Jdg.”, occurring 7 times making up 70%. The other which emerges is “Apr.” which appears only 3 times and contributes 30%.  As commonly held, “us” is narrated in more favors and fewer negatives and “them” in the opposite way to achieve planned hidden goals of persuasion.